Could Neurotracker be used as a clinical marker of recovery following pediatric mild traumatic brain injury? An exploratory study. (23rd February 2020) - Corbin-Berrigan, Laurie-Ann; Kowalski, Kristina; Faubert, Jocelyn; Christie, Brian; Gagnon, Isabelle
ABSTRACT: Primary objective: This study aimed to explore the potential for the Neurotracker, a perceptual-cognitive, multiple-object tracking test, and train paradigm, as a marker of functional recovery after mild traumatic brain injury (mTBI). It is hypothesized that Neurotracker could serve as a proxy for assessing cerebral functioning. Research design: A comparative, 6 time points, longitudinal study design was used to compare Neurotracker performance between children and adolescents who were clinically recovered from mTBI and healthy controls. Methods and Procedures: Clinical measures were collected at the initial and final visits. Neurotracker trainings were performed at each of the 6 visits. Speed thresholds (Neurotracker performance) were recorded at each visit. Main Outcomes and Results: A two-way repeated measures ANOVA suggested no differences between the groups but a significant time effect was apparent. Conclusions: Clinically recovered children and adolescents exhibit similar training abilities to control subjects on this task. These results support further investigations using Neurotracker as a marker of recovery following mTBI.